Standards of creditworthiness of customers and their impact on the liquidity of Iraqi private: Applied research in a sample of Iraqi private commercial banks (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Customers' creditworthiness standards are the key means employed by private commercial banks in assigning a suitable credit assessment for each customer. Accordingly, it had an instrumental role in indicating the degree of solvency of the potential customer before granting the required credit. The research problem reveals the nature of the relationship between the criteria of customer’s creditworthiness and banking liquidity. The most critical objectives of the study shed light on the role of using creditworthiness criteria as a tool for credit analysis of customers by banks that help reducing credit risks and thus increase banking liquidity. The questionnaire that was distributed to bank employees, the research sample, which was (8) was adopted. A bank, in addition to analyzing the financial statements of those banks listed in the Iraq Stock Exchange as a tool in collecting data related to research. The research reached a number of conclusions, the most important one is that the Central Bank of Iraq did not issue instructions according to which the model for creditworthiness criteria for customers was determined for the purpose of adoption by all commercial banks in Iraq, and then the research recommended a set of recommendations that need to be taken. The competent authorities take appropriate measuresKeywords: (criteria, customer’s creditworthiness, liquidity, private commercial banks).